Heart Failure Primary Prevention: What Does SPRINT Add?. Issue 6 (June 2021) - Raby, Kirsten; Rocco, Michael; Oparil, Suzanne; Gilbert, Olivia N.; Upadhya, Bharathi
Abstract : Hypertension is the most prevalent modifiable factor for the development of heart failure. However, the optimal blood pressure (BP) target for preventing heart failure remains uncertain. The SPRINT (Systolic BP Intervention Trial) was a large, randomized open-label trial (n=9361 participants) that showed the superiority of a systolic BP target of <120 mm Hg compared with <140 mm Hg, with a 36% lower rate of acute decompensated heart failure (ADHF) events. This beneficial effect was consistent across all the key prespecified subgroups, including advanced age, chronic kidney disease, and prior cardiovascular disease. Participants who had an ADHF event had a markedly increased risk of subsequent cardiovascular disease events, including recurrent ADHF. Randomization to the intensive arm did not affect the recurrence of ADHF after the initial ADHF event (hazard ratio, 0.93 [95% CI, 0.50–1.67]; P =0.81). A separate analysis demonstrated that the reduction in ADHF events in the intensive treatment group in SPRINT was not due to the differential use of diuretics between the 2 treatment groups. Although intensive BP treatment resulted in a lower cardiovascular disease event rate, this was not significantly associated with changes in left ventricular mass, function, or fibrosis, as assessed in SPRINT HEART, an ancillary study to SPRINT. Intensive BP treatment, however, significantly attenuated increases in carotid-femoral pulse wave velocity. Overall, these data highlight the importance of preventing ADHF in high cardiovascular risk hypertensive patients by optimal BP reduction as tested in SPRINT.